A Systematic Review of the Contribution of Dance Movement Psychotherapy Towards the Well-Being of Children With Autism Spectrum Disorders - Aithal, Supritha; Moula, Zoe; Karkou, Vicky; Karaminis, Themis; Powell, Joanne; Makris, Stergios (Frontiers in Psychology, 2021)
Background: The present review provides an original examination of published literature on the use of Dance Movement Psychotherapy (DMP) as an intervention for children with an Autism Spectrum Disorder (ASD). Method: The review was systematically conducted using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A protocol consisting of four phases: identification; screening and selection; data extraction and synthesis; quality assurance was developed and registered with the PROSPERO. A search strategy was developed using population and intervention as the key concepts and ten databases were searched between 6.1.2018 to 4.4.2018 and 10.07.2021 to 20.07.2021. The intervention characteristics were extracted based on the TIDieR template for intervention description and replication checklist. Quality assessment and level of evidence of all the included studies were evaluated using the Mixed Methods Appraisal Tool (MMAT) and the Centre for Evidence-Based Medicine (CEBM) for treatment criteria. Results: Nine research studies with a total of 133 participants were identified through a systematic search process. There was only one mixed-methods study with the component of randomization found during the literature search. Collected information was synthesised in relation to (a) ways in which dance movement psychotherapists work with children; (b) data collection methods and findings. Results from the reviewed literature suggest that DMP can potentially promote various aspects of wellbeing in children with ASD. Eight out of nine studies mentioned the effects of DMP on improving different social and communication skills. However, results from quality assessments and synthesized outcomes indicate that research in DMP is still in its infancy. Conclusions: We conclude that further large-scale, high-quality studies are required to generate further evidence that explains the processes involved in DMP, the effectiveness of DMP, the relationship between therapeutic factors of DMP, and research findings for children on the autism spectrum.